PENGEMBANGAN BAHASA RESEPTIF ANAK USIA DINI DENGAN TEMAN SEBAYANYA - Sri Widaningsih; Elia Daryati (Jurnal El-Audi, 2023)
Early Years Children (EYFS) grow and develop holistically and more adequately in the social environment closest to the child, namely peers. The purpose of this research is to look at the process of receptive language development of AUD with their peers. The design of this research is descriptive qualitative research. This research was conducted to obtain answers to existing problems and collected data in the form of words or descriptions and not numbers. this research uses the Triangulation technique with several stages, namely data collection, data reduction, data presentation, and conclusion drawing/verification. The conclusion is that AUD's receptive language development is very effectively done with peers because it is very natural, fun, effective, and explorative in nature. The implication is to develop other types of language effectively and efficiently, especially with the development of receptive language which automatically develops the cognitive and physical motor potential of children.